Socialization of the Application of Internet of Things (IoT) Technology for Temperature and Humidity Control in Oyster Mushroom Cultivation for Women Farmers Groups at the Takalar Mushroom House - Salam, Andi Ejah Umraeni; Subir, Ade Nur Fatimah; Suyuti, Ansar; Manjang, Salama; ., Yusran; Akil, Yusri Syam; Said, Sri Mawar; Kitta, Ikhlas; A, Hasniaty; Arief, Ardiaty; Dewi, Dianti Utami; B, Ian Adrian (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
This community service activity was conducted by the Department of Electrical Engineering, Hasanuddin University, in collaboration with the Women Farmers Group (Kelompok Wanita Tani/KWT) Rumah Jamur Takalar in Takalar Regency. The program was initiated to address low efficiency and unstable temperature and humidity conditions in oyster mushroom (Pleurotus ostreatus) cultivation houses, which were previously managed manually. The main objective was to improve the knowledge and technical skills of mushroom farmers in understanding and applying Internet of Things (IoT) technology for automatic environmental monitoring and control. The activity was grounded in the concept of IoT-based smart farming, integrating temperature and humidity sensors, a microcontroller, and the Blynk application for real-time environmental supervision. The implementation stages included device design, system socialization and demonstration, and evaluation through pre- and post-activity questionnaires. A total of 15 KWT participants and 4 vocational students were actively involved in the training sessions. The results showed a significant enhancement in participants’ understanding, with the average knowledge score increasing from 2.0 (low awareness) to 4.0 (good understanding), indicating a 100% improvement after training. Participants also demonstrated high enthusiasm during the activities, actively engaging in discussions, operating the Blynk application, and recognizing the advantages of automated systems in maintaining stable temperature and humidity levels in mushroom cultivation houses. The impact of this program was reflected not only in improved knowledge but also in greater awareness and interest among participants in adopting IoT technology for their farming practices. Overall, the activity effectively introduced simple yet relevant technological innovations for small-scale farmers.